2023
DOI: 10.1002/cbf.3864
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microbiome in kidney diseases: A narrative review

Kumaresan Ramanathan,
Giri Padmanabhan,
Henok Gulilat
et al.

Abstract: Many research has been conducted since the microbiota's discovery that have focused on the role it plays in health and disease. Microbiota can be divided into categories like intestinal, oral, respiratory, and skin microbiota based on the specific localized areas. To maintain homeostasis and control immunological response, the microbial populations live in symbiosis with the host. On the other hand, dysbiosis of the microbiota can cause diseases including kidney diseases and the deregulation of body functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
0
0
Order By: Relevance
“…Nevertheless, it remains unclear how the salivary microbiota of DGF patients varies, how it differs from that of IGF patients, and whether the salivary microbiota data of DGF patients possess clinical significance in prediction. While no specific research has yet directly explored the potential connection between the microbiota in the digestive tract and DGF, several studies have identified changes in salivary microbiota accompanying various kidney diseases (Ramanathan et al 2023 ). Furthermore, salivary microbiota has been implicated in the occurrence and progression of various systemic diseases, such as diabetes, cancer (Belstrøm 2020 ), hypertension (Chen et al 2023 ), Alzheimer’s disease (Lu et al 2022 ), and serves as a non-invasive biomarker in their diagnosis (Zhang et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it remains unclear how the salivary microbiota of DGF patients varies, how it differs from that of IGF patients, and whether the salivary microbiota data of DGF patients possess clinical significance in prediction. While no specific research has yet directly explored the potential connection between the microbiota in the digestive tract and DGF, several studies have identified changes in salivary microbiota accompanying various kidney diseases (Ramanathan et al 2023 ). Furthermore, salivary microbiota has been implicated in the occurrence and progression of various systemic diseases, such as diabetes, cancer (Belstrøm 2020 ), hypertension (Chen et al 2023 ), Alzheimer’s disease (Lu et al 2022 ), and serves as a non-invasive biomarker in their diagnosis (Zhang et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%